(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This study determined the Librarians’ Indices on Utilization of Electronic Information Resources in Bowen University Iwo. Three research questions and three null hypotheses were formulated to guide the study. The study covered librarians’ (academic librarians) of Bowen University Iwo. Ex-post facto research design was used for the study. The population of the study was 7 academic librarians’. Census sampling technique was used for the study; and a sample size of 7 academic librarians was used. The instrument titled “Librarians’ Indices and Utilization of Electronic Information Resources Questionnaire (LIUEIRQ)” was developed by the researcher and validated by three librarians. Cronbach Alpha reliability method was used to compute the reliability of the research instrument which yielded a co-efficient of .72. The data collected were analyzed using mean and standard deviation for research question 1- 3, and t-test was used to test null hypotheses 1- 3. All the null hypotheses were tested at .05 level of significance. The findings indicated that librarians’ indices influenced the level of utilization of electronic information resources in Bowen Universities Iwo. The study concluded that Librarians’ Indices are significant determinants for the influence in the utilization of electronic information resources in Bowen University Iwo. Librarians’ indices and utilization of electronic information resources in Bowen University Iwo is very crucial for acquiring current, timely, relevant and up-to-date electronic information resources for academic activities. Based on the findings, the study recommended among others, that the librarians’ indices should not be barrier on their utilization of electronic information resources. Every librarian should be able and interested in making use of electronic information resources no matter of their status